Data on occurrence of Gonyostomum semen in brown water lakes - Lindström, Eva S. (Uppsala University, 2018)
Algal blooms occur frequently in lakes and oceans and the causes and consequences of those are often studied. This dataset focus on a less well known type of algal bloom by the freshwater raphidophyte Gonyostomum semen. This species’ abundance and occurrence is increasing, especially in brown water lakes, the most abundant lake type in the boreal zone.
The aim of the study was to investigate which environmental factors are associated with G. semen by statistical evaluation of field data of 95 Swedish lakes over five years (2010–2014). We focused the analyses on the August data, where we had the most complete dataset, and as it is a period when G. semen can be abundant and form blooms.
Phytoplankton was sampled from boat in August by taking a water sample from the epilimnion with a 2-m long Plexiglas tube sampler (diameter = 3 cm). In lakes with a surface area >1 square km a single mid-lake site was used for sampling. In lakes with a surface area <1 square km , five random epilimnetic water samples were collected, and mixed to form a composite sample from which a subsample was taken for analysis. Samples for phytoplankton analyses were preserved with Lugol’s iodine solution (2 g potassium iodide and 1 g iodide in 100 mL distilled water) supplemented with acetic acid. Gonyostomum semen cell counts were used as a measure of abundance in each lake. Cell abundances of G. semen were estimated within the monitoring program framework from phytoplankton samples using an inverted light microscope according to the Utermöhl technique.
To characterize the physical and chemical environment of the lakes, the following parameters from the database were used: latitude (Xcoord), longitude (Ycoord), surface water temperature (Temp), pH, conductivity measured at 25 °C (Cond), calcium (Ca), magnesium (Mg), sodium (Na), potassium (K), alkalinity (Alk), sulphate (SO 4 ), chloride (Cl), ammonium-nitrogen (NH4), total nitrogen (TotN), total phosphorus (TotP), water color measured as absorbance
of 0.45 μm filtered water in a 5 cm cuvette (AbsF420), silicon (Si), turbidity (Turb), total organic carbon (TOC), iron (Fe), and manganese (Mn). The chemical parameters were from the sample taken at 0.5 m depth and measured according to international (ISO) or European (EN) standards (SS-EN ISO 5667-1:2007.
In 2014 additional water samples were collected during the monitoring sampling and the water from 72 of the 95 lakes was filtered through 0.22 μm supor filter within 1 day of sampling for visible and fluorescence spectra measurements in order to characterize DOM quality. Absorbance scans were performed between 230–600 nm using a 1-cm quartz cuvette. The specific UV absorbance of organic carbon (SUVA254 ) was then calculated by dividing the decadic absorption coefficient at 254 nm by the DOC (dissolved organic carbon) concentrations.
For further information, see article "High abundances of the nuisance raphidophyte Gonyostomum semen in brown water lakes are associated with high concentrations of iron" by Lebret et al (2018).
The dataset was originally published in DiVA and moved to SND in 2024.

Se engelsk version av denna katalogpost för information om data och insamling.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Data on occurrence of Gonyostomum semen in brown water lakes
High abundances of Gonyostomum semen in brown water lakes are associated with high concentrations of iron : Fluorescence and abosrbance data
Keywords: fluorescence; fluorescens; lakes; sjöar; iron; järn; algae; alger; algal bloom; algblomning; Ecology; Ekologi